Gender Stereotypes and Female Beauty Standards (Content Analysis of the Instagram Account @ratughania) - Aisah Anggraeni Yudiantika; Ninuk Sholikhah Akhiroh (Journal of Feminism and Gender Studies, 2026)
This study aims to analyze representations of female beauty and gender stereotypes in Instagram content, focusing on the @ratughania account. The approach used was qualitative, employing digital ethnography and content analysis of visual posts and audience interactions in the comments section. Data were obtained from photos, videos, and captions uploaded to the @ratughania account in February 2023. This analysis is based on Peter L. Berger and Thomas Luckmann's social construction theory and Naomi Wolf's concept of beauty to understand how beauty standards are shaped on social media. The results show that beauty standards on social media still emphasize physical perfection, such as clear and acne-free skin, which leads to negative judgments of women with acne. The study also found forms of resistance to these stereotypes through content and audience responses. The @ratughania account openly displays representations of beauty with acne and promotes self-acceptance, while positive comments from followers create a digital space that builds solidarity among women.